FUNCTIONAL ACTIVITY OF ELDERLY PATIENTS AFTER STROKE - Andriy O. Golyachenko; Igor R. Mysula; Iryna I. Kamyshna; Oleksandr A. Holyachenko (Клінічна та профілактична медицина)
Introduction. A history of severe neurological disease often has an impact on the patient's future life. This applies to all aspects of a person's life – functional, social, mental, and spiritual.